Analisis Pecahan Batu Bata Merah Sebagai Pengganti Agregat Halus Dalam Campuran Beton Ringan: Penelitian - Dwi Aditya Yanuar; Afrie Nardiansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The excessive exploitation of natural sand has caused environmental impacts, thus innovation is needed in utilizing environmentally friendly alternative materials for construction. One such alternative is the use of red brick waste as a partial substitute for fine aggregate in concrete mixtures. This study aims to determine the compressive strength of concrete using 50% red brick waste as a replacement for fine aggregate. The research method used an experimental approach with two types of mixtures: normal concrete and concrete with 50% red brick substitution. Compressive strength tests were conducted at 7, 14, and 28 days of curing. The results showed that normal concrete achieved 73%, 87.55%, and 105.35% of the design strength (fc’ = 20 MPa), while the concrete with 50% red brick substitution reached only 63.1%, 76.2%, and 91.5%. The red brick concrete showed lower compressive strength compared to normal concrete, but its strength continued to increase consistently over time. These results indicate that red brick waste has potential as an alternative fine aggregate, especially for non-structural applications.